Methods to Estimate Willingness-to-Pay Per Quality Adjusted Life Year as Cost-Effectiveness Threshold - Tri Murti Andayani; Dwi Endarti; Susi Ari Kristina; Rifqi Rokhman (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Pharmacoeconomic studies, especially the cost-utility analysis method, require a cost-effectiveness threshold for interpretation of the cost-effectiveness ratios of the study. The cost-effectiveness threshold is determined by each country. Therefore, a study to determine the Willingness-To-Pay per Quality Adjusted Life Year (WTP per QALY) as cost effectiveness threshold for pharmacoeconomic studies is indispensable in Indonesia. The purpose of this study is to review the literature and to develop guidelines for estimating WTP per QALY as cost effectiveness threshold in pharmacoeconomic studies. Literature review was conducted using some electronic databases, such as MEDLINE, Pubmed, Science Direct, and Google Scholar. The study was conducted by holding survey on healthy population or patients. Estimated WTP per QALY are differentiated based on therapy for preventive, curative, and life saving or interventions that can prolong life expectancy. The study was conducted in three stages: measuring utility, measuring WTP, and combining WTP and utility values in WTP per QALY. Utility measurements are performed either with single or multi-attribute instruments, whereas WTP measurements use contingent valuation or discrete methods. Survey technique can be done with face to face interview, telephone, and internet. This research can be used as a guide in the development of methods to estimate WTP per QALY as cost effectiveness threshold in pharmacoeconomic studies.